1997
DOI: 10.1115/1.2819111
|View full text |Cite
|
Sign up to set email alerts
|

On End-Wall Corner Vortices in a Lid-Driven Cavity

Abstract: with a primary eddy, downstream and upstream secondary eddies, and possibly meandering Taylor-Gortler longitudinal vortices as the Reynolds number is sufficiently high (see Fig. 1(a)). Previous investigations, however, did not focus much on the end-wall corner vortices other than noting their existence. This motivated us to conduct the present study with an aim to improve our understanding of comer vortices present near the end wall of the lid-driven cavity.We conducted a flow simulation to study the laminar f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 13 publications
1
18
1
Order By: Relevance
“…(1988) as local and global #ow features. The local eddies, the so-termed corner vortices, located close to the cavity span end-walls, take a large part in spanwise #uid transport (Chiang et al 1997). The global eddies, commonly referred to as Taylor}Goertler-like vortices, are represented by several dispersed counter-rotating vortex pairs (depending on #ow regime and cavity spanwise ratio) which can meander along cavity span (Kose!…”
Section: Introductionmentioning
confidence: 99%
“…(1988) as local and global #ow features. The local eddies, the so-termed corner vortices, located close to the cavity span end-walls, take a large part in spanwise #uid transport (Chiang et al 1997). The global eddies, commonly referred to as Taylor}Goertler-like vortices, are represented by several dispersed counter-rotating vortex pairs (depending on #ow regime and cavity spanwise ratio) which can meander along cavity span (Kose!…”
Section: Introductionmentioning
confidence: 99%
“…The code has been examined using both analytical and numerical examples given in [12]; the numerical examples used for the validation include both 2-dimensional and 3-dimensional cavity flow fields. A detailed description of these validation studies can be found in [15].…”
Section: Code Validationmentioning
confidence: 99%
“…The literature available for pressure/flow simulation in cavities is quite vast and the SIMPLE (semi implicit method for pressure linked equation) family algorithm [27] has been widely applied to this kind of simulation. Most of the work has been done for rectangular cavities [28][29][30][31][32][33][34] where Cartesian coordinates were applied. Literature available on cavities in cylindrical coordinates [35][36][37] is much less common.…”
Section: Introductionmentioning
confidence: 99%